Wetland Faunal Survey of Sone Gharial Sanctuary in Madhya Pradesh - Sharma, R. K.; Sharma, Sanjay (Indian Forester, 1997)
The faunal survey conducted in Sone Gharial Sanctuary of Madhya Pradesh during 1996 is reported in this paper. 35 Gharials (Gavialis gangeticus),11 Mugger Crocodiles (Crocodylus palustris), Turtles, Otters, Birds and Insects sighted are described.